Comparative Outcome Analysis of Endoscopic Third Ventriculostomy and Ventriculoperitoneal Shunt Surgery in Pediatric Hydrocephalus: An Experience of a Tertiary Care Center - Prajapati, Hanuman Prasad; Ansari, Mohd Ahmad; Jaiswal, Manish (Asian Journal of Neurosurgery, 2022)
Background Endoscopic third ventriculostomy (ETV) and ventriculoperitoneal shunt surgery (VPS) are used for the surgical management of pediatric hydrocephalus. There is controversy regarding the safety and efficacy of these procedures according to age, etiologies, and type of hydrocephalus.Objective The purpose of this study was to compare the outcomes and complications of ETV and VPS in pediatric hydrocephalus and to evaluate the better procedure.Material and Methods We retrospectively analyzed the pediatric hydrocephalus cases that were operated by ETV and VPS at our department from June 2016 to June 2019. Data were analyzed with respect to the etiology of hydrocephalus, age, and gender of the patients. We compared the outcomes (success and failure) depending on age at surgery, etiology, and type of hydrocephalus, complications at 12 months of follow-up. Fisher's exact test and chi-square test were applied to test the significance of difference.Results There were 195 pediatric hydrocephalus cases, which were operated by ETV (n = 43; 22.05%) and VPS (n = 152; 77.95%). The mean age of the cases was 53.63 ± 60.24 (ranged 0.5–204 months) in the ETV group and 53.44 ± 54.10 (ranged 0.3–210 months) in the VPS group. The male-to-female ratio was 1.41:1 in the ETV group and 1.21: 1 in the VPS group. Overall, ETV had successful outcomes in 30(69.77%) cases and VPS in 102(67.11%) cases at 12 months of follow-up. The complication rates were found in 7 (16.28%) cases in the ETV group and 38 (25.0%) cases in the VPS group. At initial 0.5 months of follow-up, ETV required revisions in 6 (13.95%) cases and VPS in 15 (9.87%) cases.Conclusion Although the success and failure of both the procedure vary according to the age at surgery, etiology and type of hydrocephalus, and complications, and failure rates on follow-up, there were no statistically significant differences between the two surgical groups in respect to these variables.
Keywords: Pediatric hydrocephalus; ETV; VPS; Outcomes; complications